S66 Targeted in Vivo Imaging of the αvβ6 Integrin in Mice with Bleomycin-Induced Lung Fibrosis. (19th November 2012) - John, AE; Luckett, J; Awas, R; Habgood, A; Ludbrook, S; Blanchard, A; Perkins, A; Jenkins, RG; Marshall, JF
Abstract : Introduction: TGFβ activation by αvβ6 integrins is central to the pathogenesis of idiopathic pulmonary fibrosis (IPF). Furthermore, αvβ6 expression is increased in both human, and murine, fibrotic lung tissue. Current assessment of αvβ6 integrin levels in the lung requires immunohistochemical analysis of biopsy samples and repeated measurement of αvβ6. Although αvβ6 may be useful as a biomarker in IPF, currrent methods of detection make this approach clinically impractical. We have developed a non-invasive radioimaging CT/SPECT strategy for measuring αvβ6 integrin levels in the lungs facilitating the monitoring of disease progression and therapeutic response in IPF. Methods: C57Bl/6 mice received intratracheal bleomycin or saline, 28 days prior to intravenous injection with Indium111-labelled A20FMDV2, an αvβ6 binding peptide derived from the VP1 coat protein of foot-and-mouth virus. A scrambled sequence peptide was used as control. Mice were injected with 5µg (10–24MBQ) of peptide and imaged by CT/SPECT scanning one, and three, hours later. Results: Maximal binding of Indium 111 -labelled A20FMDV2 peptide was detected in skin, and lungs, of all mice at one hour. No significant binding was detected in mice injected with control peptide. Binding to αvβ6 integrin was significantly higher in the lungs of bleomycin, compared with saline, exposed mice (0.12±0.01MBQ vs 0.06±0.009 p<0.001). Label was detected at similar levels in the bladder and kidneys of all mice suggesting similar administration and excretion kinetics. Conclusions: Indium 111 -labelled A20FMDV2 peptide can specifically detect increased levels of αvβ6 integrin in the lungs of injured mice demonstrating that non-invasive imaging of the αvβ6 integrin in the development of fibrosis is possible.